Outcomes and comparations of pediatric surgery about choledochal cyst with robot-assisted procedures, laparoscopic procedures, and open procedures: A meta-analysis - Xie, Siqi; Huang, Yanbing; He, Yuanbin; Liu, Mingkun; Wu, Dianming; Fang, Yifan (Frontiers in Pediatrics, 2022)
Background: Choledochal cysts (CC) are rare entities characterized by congenital biliary tract dilatation of the intrahepatic or extrahepatic bile ducts and often associated with pancreaticobiliary maljunction. Robot-assisted surgery has been able to complete almost all pediatric endoscopic surgery nowadays. But evidence of the postoperative outcomes of robotic-assisted operation is limited, comparing with the laparoscopic operation and traditional open operation. The aim of this meta-analysis was to identify the advantages and deficiencies about robotic-assisted operation for choledochal cysts. Methods: A meta-analysis of retrospective studies published in PUBMED, MEDLINE, Web of Science and China National Knowledge Infrastructure (CNKI). No date limit was used, with the last search on April 30, 2022. No publication restrictions or study design filters were applied. Results: Nine retrospective cohort studies with 1395 patients (366 in the robotic-assisted operation group (RG), 532 in the laparoscopic operation group (LG) and 497 in the open operation group (OG)) were enrolled in our study. Subgroup analysis demonstrated the RG had significant longer operative time (standardized mean difference (SMD) = 1.59, 95% CI = (0.02, 3.16), P <0.05), less blood loss (SMD =-1.52, 95% CI = (-2.71, -0.32), P <0.05), shorter enteral feeding time (SMD =-0.83, 95% CI = (-1.22, -0.44), P <0. 001), shorter time to stay in the hospital (SMD =-0.81, 95% CI = (-1.23, -0.38), P <0. 001), fewer postoperative complications (Relative risk (RR) =1.09, 95% CI = (1.04, 1.13), P <0. 001) but higher expenses (SMD = 8.58, 95% CI = (5.27, 11.89), P <0. 001) than LG. While a significant older age (SMD = 0.46, 95% CI = (0.26, 0.66), P <0. 001), longer operative time (SMD = 3.96, 95% CI = (2.38, 5.55), P <0. 001) and shorter time to stay in the hospital (SMD = -0.93, 95% CI = (-1.62, -0.25), P <0.05) than OG. Conclusions: Laparoscopic and robotic-assisted procedure are both safe and minimal invasive operational maneuvers. Robotic-assisted procedure may slowly surpass and has a trend to replace laparoscopy for its advantages. More experiences should be accumulated for the unexpected complexities, so as to be more stable in the younger age of children.